Mindful movement : the evolution of the somatic arts and conscious action - Eddy, Martha (Intellect Books, 2016)
This book uses original interviews, case studies, and practice-led research to define the origins of a new holistic field--somatic movement education and therapy--and its impact on fitness, ecology, politics, and performance. It reveals the role dance has played in informing and inspiring the historical and cultural narrative of somatic arts. Providing an overview of the antecedents and recent advances in somatic study and with contributions by diverse experts, it highlights the role of Asian movement, the European physical culture movement and its relationship to the performing arts, and female perspectives in developing somatic movement, somatic dance, social somatics, somatic fitness, somatic dance and spirituality, and ecosomatics.